Development and evaluation of centella asiatica powder by freeze drying : comparison of extraction methods on yield and hygroscopicity - Siti Nur Arisha, Muhamad Zulkarnain (2019)
Novel techniques and the development of new methods has provided an opportunity to obtain highly purified natural bioactive compound extracts with potential for the treatment and prevention of various diseases. This research compares the percentage yield of Centella asiatica obtained through freeze drying that was aqueous-extracted earlier by conventional extraction method (decoction and infusion) and an advanced non-conventional extraction method; ultrasound-assisted extraction (UAE).The physical stability of the powder obtained was then tested by hygroscopicity test. The studies were conducted using gravimetric sorption analysis method with slight modification. Each of the powder samples was subjected to the pretreatment at 45 °C, 10% RH followed by equilibrating at 25 °C, 80% RH and individually categorized as per European Pharmacopeia. UAE generated the highest powder yield (11.65%) followed by infusion (10.48%) and decoction (10.03%). After 24 hours of hygroscopicity analysis, all three samples were found to be very hygroscopic since their respective percentage of water sorption was more than 15%. The highest percentage of water sorption was by decoction (71.31%), followed by infusion (71.28%) and lastly UAE (68.71%).